Primary anal melanoma with visceral dissemination: a case presentation - Huanay-Martínez, Diego Armando (2025)
Primary anal melanoma accounts for less than 2% of all melanomas and anal tumors. It is highly aggressive, and its nonspecific clinical presentation can delay diagnosis. Despite advances in immunotherapy, surgical resection remains the only curative treatment in early stages. We report a case of a patient presenting with rectal bleeding and an anal mass, without involvement of the skin, eyes, or gastrointestinal tract. Immunohistochemistry was positive for S-100 and Melan-A. Hepatic and pulmonary metastases were identified, and the clinical course was unfavorable.